2018
DOI: 10.1007/s12072-018-9890-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple doses of hepatitis B recombinant vaccine for chronic hepatitis B patients with low surface antigen levels: a pilot study

Abstract: In low-level HBsAg CHB patients, serial HBsAg-based vaccinations were safe, resulting in significant HBsAg decline. HLA gene expression and genotypes played a role in vaccine responsiveness (ClinicalTrials.gov Identifier: NCT01817725).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…More promising results were obtained by administration of recombinant vaccine in people with low HBsAg levels, which was associated with further reductions in HBsAg titres and undetectable HBsAg in some participants. However, there was no prospective control arm in this study ( 91 ). Larger randomized studies are warranted to assess whether recombinant vaccines have a role in treating individuals with low baseline HBsAg levels.…”
Section: Previous Clinical Trials Of Therapeutic Vaccination In Chronic Hbvmentioning
confidence: 95%
“…More promising results were obtained by administration of recombinant vaccine in people with low HBsAg levels, which was associated with further reductions in HBsAg titres and undetectable HBsAg in some participants. However, there was no prospective control arm in this study ( 91 ). Larger randomized studies are warranted to assess whether recombinant vaccines have a role in treating individuals with low baseline HBsAg levels.…”
Section: Previous Clinical Trials Of Therapeutic Vaccination In Chronic Hbvmentioning
confidence: 95%
“…Thus, the rational selection of patients with low levels of serum HBsAg after long term NAs treatment could be employed to optimize the therapeutic efficacy of B cell targeting vaccination. Indeed, in a recent study, conventional HBsAg-based vaccination in 20 HBeAg-negative patients with HBsAg <1,000 IU/ml, resulted in a significant HBsAg decline in 14 patients and HBsAg loss in 2 patients (128). In another study, the switch from long-term entecavir (ETV) treatment to a combined therapy with IFN-alpha-2b, HBsAg-based vaccination, and IL-2 resulted in a higher HBsAg loss rate (9.38%) compared to IFN-alpha-2b (3.03%) alone or continued entecavir (3.70%) therapy in HBeAg-negative patients.…”
Section: How To Optimize the Therapeutic Efficacy Of Strategies Targementioning
confidence: 99%
“…Therefore, therapeutic effect of B cells targeted vaccination could be optimized through selecting reasonably upon patients with low HBsAg levels who have been treated with NAs for a long time. Actually, a recent study enrolled 20 patients with negative HBeAg as well as HBsAg < 1000 IU/ml and found that HBsAg decreased significantly in 14 patients, and 2 patients had a HBsAg loss after inoculated conventional HBsAg-based vaccination ( 96 ). Another research showed that for HBeAg-negative patients, switching from long-term ETV therapy to adding HBsAg-based vaccination, IFNα-2b and IL-2 as a combination, there was a higher rate of HBsAg loss (9.38%) compared with patients using IFNα-2b alone (3.03%) or continuing entecavir (3.70%) treatment .…”
Section: Chb Functional Cure and Host Immune Responsementioning
confidence: 99%